1977
DOI: 10.1126/science.302031
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Limb Tissue Affects Neurite Growth in Spinal Cord Cultures

Abstract: Limb bud mesenchyme enhances and directs the growth of tadpole spinal cord nerve fibers in tissue culture. This effect on elongating neurites may involve alterations in nerve-substratum interactions by the presence of undifferentiated target tissues. The relationship between nerve fibers and their potential innervation sites can explain directed nerve growth to the developing limb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1979
1979
1997
1997

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 15 publications
(3 reference statements)
0
9
0
Order By: Relevance
“…Chen and Levi-Montalcini (1970) showed that explanted embryonic foregut tissue was necessary for in vitro fibrillar growth from embryonic neurons of the cockroach Periplaneta americana. Pollack and Liebig (1977) showed that differentiating limb bud tissue had a trophic influence on cultured frog spinal cord explants. Conditioning the medium in Helisoma enhanced neurite outgrowth in cultured buccal ganglia to levels comparable to in uiuo growth.…”
Section: Growth Characteristics Of Isolated Helisoma Neuronsmentioning
confidence: 99%
“…Chen and Levi-Montalcini (1970) showed that explanted embryonic foregut tissue was necessary for in vitro fibrillar growth from embryonic neurons of the cockroach Periplaneta americana. Pollack and Liebig (1977) showed that differentiating limb bud tissue had a trophic influence on cultured frog spinal cord explants. Conditioning the medium in Helisoma enhanced neurite outgrowth in cultured buccal ganglia to levels comparable to in uiuo growth.…”
Section: Growth Characteristics Of Isolated Helisoma Neuronsmentioning
confidence: 99%
“…Our recent studies have detailed the growth interactions between the efferent nerve fiber of the spinal cord and its primary target, the limb ( Fig. 1) [Pollack and Liebig, 1977; Muhlach and Pollack, 19821. Limb tissue is most effective as a target for spinal nerve fibers when it is least differentiated, or essentially a mesenchymal limb bud.…”
mentioning
confidence: 99%
“…Pollack and Muhlach paradigms of tissues derived from the spinal cord, dorsal root ganglion (DRG) and hindlimb of the frog tadpole (Rana pipiens) have provided much of the evidence that a temporal dependence is superimposed on the actions of targets in eliciting nerve growth and survival [Pollack and Liebig, 1977;Pollack et al, 1979;Pollack et al, 1980; Pollack and Muhlach, 19811. Drawing upon the results of recent experiments carried out in our laboratory, together with some newly attained information regarding substratum influences and biochemical indices of neural maturation, we have formulated a model to explain the timed action of targets on the growth and survival of neural centers related to the formation of the reflex arc.…”
mentioning
confidence: 99%
“…Chamley, Goller & Burnstock, 1973;Coughlin, 1975;Ebendal & Jacobson, 1977;Pollack & Liebig, 1977;Lumsden & Davies, 1983). With the exception of recent work on sensory nerves in mouse (Lumsden & Davies, 1983), these studies have been of denervated target tissues and regenerating axons.…”
Section: Introductionmentioning
confidence: 99%